A Halogen‐Bond Donor Catalyst for Templated Macrocyclization. (5th September 2019) - Guillier, Kévin; Caytan, Elsa; Dorcet, Vincent; Mongin, Florence; Dumont, Élise; Chevallier, Floris
Abstract: A halogen‐bond templated 1:1 macrocyclization in solution is reported. Tetra(iodoperfluorophenyl) ethers were used as halogen‐bonded exotemplates in a substoichiometric amount (5 mol %). Pyridine‐containing macrocyclic architectures were formed by ruthenium‐catalyzed tandem metathesis/transfer hydrogenation sequence using sodium borohydride and methanol as non‐dihydrogen hydrogen source. The halogen‐bonded stabilization energies were analyzed relying on density functional theory. Abstract : Iodperfluorphenylether wurden als Exotemplate in substöchiometrischen Mengen eingesetzt, um eine halogenbrückenvermittelte 1:1‐Makrozyklisierung von Pyridinderivaten durch Tandem‐Olefinmetathese/Transferhydrierung durchzuführen.